Modelagem ecológica e manejo de populações de pragas: Uma conexão possível e necessária para um mundo em transformação - Lima, Ernesto A.B.F. [UNESP]; Ferreira, Claudia P. [UNESP]; Godoy, Wesley A.C. (Springer Nature, 2009)
Ecological modeling is an important tool for investigating dynamic behavior patterns in populations, trophic interactions, and behavioral ecology. However, the ecological patterns that reflect population oscillation trends are often not clearly visible without analytical instruments such as ecological models. Thus, ecological modeling plays a fundamental role in describing demographic processes that are important for population dynamics. Ecological models, besides making possible the visualization of ecological patterns, may also reveal patterns of population persistence in many trophic systems, including prey-predator or host-parasitoid relationships, interactions that are commonly present in integrated pest management programs. In this forum, we present the main ecological aspects important for model building and implementation of integrated pest management programs for insects. Particularly, in this study, we analyze the combination between host-parasitoid models and the concept of economic threshold level on a spatio-temporal scale. As a conclusion about the model combination, spatial structure is essential for models of this nature, since its introduction into the system significantly alters the economic threshold-level values.
Ecological modeling and pest population management: A possible and necessary connection in a changing world
Keywords: Integrated pest management; Mathematical model; Theoretical ecology